2016
DOI: 10.1016/j.chemosphere.2015.09.106
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin expression in wild cyprinid Petroleuciscus esfahani as a biomarker of endocrine disruption along the Zayandeh Roud River, Iran

Abstract: Aquatic environments are the ultimate sink for most of anthropogenic pollutants. The Zayandeh Roud River is the most important river in the central Iranian Plateau, supplying water to a large population. In order to determine the potential occurrence and in vivo effects of Endocrine Disrupting Chemicals (EDCs) with estrogenic or anti-androgenic properties we analyzed the wild populations of an extensively distributed endemic fish species, Petroleuciscus esfahani. For this purpose, specimens were caught from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The GSI of males and females exposed to the highest concentration (250 µg/L) was lower, which indicated a stress symptom. The decrease in GSI might be associated with endocrine-active substances [47,48]. Similarly, GSI was not affected in Javanese medaka exposed to estrone, an EDC [43].…”
Section: Discussionmentioning
confidence: 89%
“…The GSI of males and females exposed to the highest concentration (250 µg/L) was lower, which indicated a stress symptom. The decrease in GSI might be associated with endocrine-active substances [47,48]. Similarly, GSI was not affected in Javanese medaka exposed to estrone, an EDC [43].…”
Section: Discussionmentioning
confidence: 89%
“…However, males and juvenile fish can also synthesize Vtg if exposed to exogenous oestrogen or oestrogen mimics (Bjorkblom, Salste, Katsiadaki, Wiklund & Kronberg, 2008). Thus, elevated Vtg levels in males and juveniles have been proposed as an excellent biomarker for environmental oestrogens (Gilannejad et al, 2016;Vajda et al, 2011). To date, numerous methods mainly employing immunoassays based on purified Vtg and its antibody have been developed for the quantification of piscine Vtg (Garnayak, Mohanty, Rao, Sahoo & Sahoo, 2013;Maltais & Roy, 2009).…”
Section: Shemeshmentioning
confidence: 99%
“…Many studies have reported that Vtg also plays nonreproductive roles as an immune-related molecule that is associated with defense reactions and by participating in environmental stress responses by recognizing cell damage through membrane binding and improving cell oxidative stress tolerance [66][67][68]. As such, Vtg is a biomarker for environmental stress, particularly for endocrine-disrupting chemicals [69,70]. In the present study, Vtg translation was upregulated by approximately 20-fold in the gonads of female oysters exposed to 500 mg L À1 Zn for 30 d.…”
Section: Differential Effects Of Zn Exposure On Male and Female Oystersmentioning
confidence: 99%